261 THE EPIDEMIOLOGY OF EXTRAHEPATIC BILIARY ATRESIA AND ACUTE LIVER FAILURE AS INDICATIONS FOR LIVER TRANSPLANTATION. (1st January 2005) - Paravar, T.; Venick, R; Narsinh, K.; Rhee, C.; Molina, R.; Katzir, L.; Martin, M. G.
Abstract : Objectives: Extrahepatic biliary atresia (EHBA) and acute liver failure (ALF) respectively account for 40-50% and 10-20% of all pediatric liver transplants in the United States. The objective of this study was to learn more about the epidemiology of both EHBA and ALF in those children who where listed for liver transplantation. Methods: The United Network for Organ Sharing (UNOS) database of all patients who were listed as needing liver transplantation from 1987 to 2002 was used for analysis after excluding patients over age 18, patients with a previous transplantation, and patients that had neither ALF nor EHBA. Patients with ALF were subdivided by etiology. Mean age of listing, gender, ethnicity, state of residence, need for ventilator, and outcome were compared between patients with EHBA, ALF, and subgroups of ALF. Results: 2198 of 4279 patients presented with EHBA. Patients with EHBA (mean age = 3.2) were significantly younger than those with ALF (mean age = 7.5). The oldest age group were patients with Tylenol overdose as the cause of ALF (mean age = 14.4). Females were over-represented in patients with EHBA (1.4:1, p≤0.0001) and Tylenol overdose (3.2:1, p≤0.0001). African American (p≤0.0001) and Asian (p≤0.0001) populations had higher incidences of EHBA. Various states were found to have significantly greater rates of incidence of either ALF or EHBA. Finally, patients with EHBA are least likely to need a ventilator and have overall better outcomes than patients with ALF when transplanted. Conclusion: Overall, we have found that patients with EHBA, although they present at younger ages, have better outcomes. There is a female as well as nonwhite predominance of EHBA and a surprising variability by state of residence for both EHBA and ALF. We are hopeful that this study may aid in the better understanding of the epidemiology of EHBA and ALF as indications for liver transplantation, thus enabling physicians to more accurately and quickly diagnose these diseases.